A manual for the preparers and users of eco-efficiency indicators version 1.1 (UN New YorkUS, 2004)
Presents a method by which environmental and financial performance indicators can be used together to measure an enterprise's progress in attaining eco-efficiency or sustainability
Keywords: ENVIRONMENTAL INDICATORS